Disease activity prediction and prognosis of anti-GBM nephritis based on T lymphocyte subset ratios. (30th September 2021) - Zhang, Dan; Zhang, Fan; Liu, Meiling; Zhang, Mingchao; Zhang, Jiong; Wang, Jinquan
Introduction: Cell-mediated autoimmunity, especially the autoreactivity of T cells, is known to underlie the initiation of anti-glomerular basement membrane disease. However, the T lymphocyte subsets that determine the disease activity, renal fibrosis, and prognosis of anti-GBM disease have not been clearly elucidated. Methods: The T lymphocyte subsets (CD4+ and CD8+) were examined on peripheral blood and renal biopsy tissues from 65 patients with biopsy proven anti-GBM disease. Patients were divided into the high ratio group and low ratio group according to the cutoff values in the receiver operating characteristic curve analysis. The correlations of T lymphocyte subsets with clinical, pathological data, and renal outcome were analyzed. Results: By the end of follow-up, 45 patients (69.2%) developed end-stage renal disease (ESRD). In peripheral blood, the CD4+/CD8+ ratio showed a predictive ability with a sensitivity and specificity of 91.3% and 52.9%, respectively, which gave rise to a cutoff value of 0.89. There was a significant difference in the activity index between these two groups (3.91 ± 1.38 vs. 2.89 ± 1.13, p = 0.007). In the renal tissues, the CD4+/CD8+ ratio had the optimal cutoff point of 0.82 with a sensitivity of 57.8% and specificity of 85%. The renal activity index was higher for the renal tissues with high CD4+/CD8+ ratios than that of tissues with low CD4+/CD8+ ratios (4.32 ± 1.55 vs. 3.37 ± 1.41, p = 0.016). Peripheral blood CD4+/CD8+ ratios of ≥0.89 or renal tissue CD4+/CD8+ ratios of < 0.82 positively correlated with poor renal prognosis in patients with anti-GBM nephritis. Conclusions: The CD4+/CD8+ ratio was associated with renal activity index both in peripheral blood and renal tissue and predicts the renal prognosis of patients with anti-GBM nephritis.